What Men and Women Really Want: Differences in Gender-Based Evaluations of Service Recovery Efforts. Issue 1 (2nd January 2016) - Ding, May-Ching; Ho, Ching Wei; Lii, Yuan-Shuh
ABSTRACT: This article presents a model of the effects of perceived justice dimensions (distributive, procedural, and interactional) on consumer attitude (satisfaction and trust) and behavioral intention (extra-role behaviors and repurchase intention). Additionally, gender is considered as a moderating variable in the proposed model. A survey was carried out among undergraduate students in a large university in Taiwan. Findings indicate that perceived justice influences satisfaction and trust, which then mediates customer extra-role behaviors and repurchase intention. Concerning the moderator, gender, men and women pay attention to distributive justice differently.